Perancangan Media Promosi Wisata Taman Nasional Baluran Situbondo - Putra, Fuzza Duwana; Aryani, Dewi Isma (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
A national park is an area that is intended to preserve nature with the formation of native ecosystems using a zoning system. In addition to having a conservation function, national parks can be used for tourism purposes. Baluran National Park is one of the national parks in Indonesia. The name Baluran comes from Mount Baluran which is located in the Situbondo and Wongsorejo areas, Banyuwangi, East Java. Baluran National Park is considered less popular with tourists because of its location close to the islands of Bali and Lombok, making it less competitive. Baluran National Park has the potential as a tourist spot because it has a very wide savanna with a variety of wildlife, and its location is also close to the beach. Therefore, the design of promotional media is needed with the aim of introducing and being able to increase public interest in traveling to Baluran National Park through appropriate and interesting information media. The research method in this design is quantitative with observation and literature study. The results of this study were obtained in the form of design solutions in the form of promotional video designs and supporting media in the form of website advertising designs, web banners, billboards, and social media.